Implementasi Monitoring dan Metode Quality Of Service (QOS) Pada Jaringan Komputer Secara Sinkron dan Asinkron - Dwi Fitri Brianna (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
One of the network instabilities is bandwidth traffic. Therefore, it is necessary to analyze monitoring and QoS on synchronous and asynchronous computer networks by measuring QoS to overcome these problems. QoS (Quality of Service) measurement is carried out so that internet users can find out whether the quality of internet services they get is good or not. Monitoring and QoS on synchronous and asynchronous computers at pmi muara enim emphasizes the process of monitoring and measuring network quality parameters on internet network infrastructure such as access speed and transmission capacity, work, from the sender point to the destination receiver point. Based on the results of the Quality of Service (QoS) analysis on the WLAN network, it can be concluded that Packet Loss is included in the “Very Satisfactory / Very Good” category with an index of 4. Delay: Also falls into the “Very Satisfactory / Very Good” category with an index of 4. Jitter: Falls into the “Satisfactory / Good” category with an index of 3. With a percentage of QoS value of 91.66%. So based on the percentage obtained, the quality of WLAN network services falls into the “Satisfactory” category. This shows that the network can provide good performance in terms of managing packet loss, delay, and jitter so that the user experience is considered very good and meets the applicable TIPHON standards.